2017
DOI: 10.5194/esd-8-865-2017
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of Lyapunov exponents: the link between atmospheric rivers and large-scale mixing variability

Abstract: Abstract. Large-scale tropospheric mixing and Lagrangian transport properties have been analyzed for the long-term period 1979–2014 in terms of the finite-time Lyapunov exponents (FTLEs). Wind field reanalyses from the European Centre for Medium-Range Weather Forecasts were used to calculate the Lagrangian trajectories of large ensembles of particles. Larger values of the interannual and intra-annual mixing variabilities highlight the El Niño Southern Oscillation, the storm track, or the Intertropical Converge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Its high altitudes pose a barrier to low and midtropospheric zonal flow. This barrier to the zonal flow deflects the climatological sea-to-land easterly flow as it enters the continent from the equatorial Atlantic, forming a meridional channel of north-to-south moisture transport between 850 and 700 hPa (Gimeno et al, 2016) that supplies moisture for rainfall in populated areas in southeastern and southern South America (Zemp et al, 2014). When intensified, this north-to-south moisture flux characterises the South American Low-Level Jet (SALLJ, Vera et al, 2006).…”
Section: Aspects Of the Moisture Transport In South Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Its high altitudes pose a barrier to low and midtropospheric zonal flow. This barrier to the zonal flow deflects the climatological sea-to-land easterly flow as it enters the continent from the equatorial Atlantic, forming a meridional channel of north-to-south moisture transport between 850 and 700 hPa (Gimeno et al, 2016) that supplies moisture for rainfall in populated areas in southeastern and southern South America (Zemp et al, 2014). When intensified, this north-to-south moisture flux characterises the South American Low-Level Jet (SALLJ, Vera et al, 2006).…”
Section: Aspects Of the Moisture Transport In South Americamentioning
confidence: 99%
“…While water vapour is concentrated at lower levels, selecting a particular level becomes problematic near topography, such as the Andes, for two reasons: (a) topography often crosses lower tropospheric pressure levels, and (b) it causes the level of maximum moisture transport to rise in its vicinity (Insel et al, 2010). The SALLJ, 478 G. M. P. Perez et al: Convergence zones stemming from large-scale mixing for example, transports substantial amounts of water vapour and flows parallel to the Andes between 850 and 700 hPa (Gimeno et al, 2016).…”
Section: Aspects Of the Moisture Transport In South Americamentioning
confidence: 99%
“…Rutherford et al (2011) and Guo et al (2016) employed the FTLE to visualize flow features in tropical cyclones. Garaboa-Paz et al (2015) and Garaboa-Paz et al (2017) suggested that FTLE ridges are closely linked to atmospheric rivers in boreal winter, when advection shapes the spatial distribution of water vapour. The criterion for convergence zones proposed here is closely related to the framework proposed by Garaboa-Paz et al (2015) for atmospheric rivers.…”
Section: Mixing and Lagrangian Coherent Structures In The Atmospherementioning
confidence: 99%
“…To analyze the contribution of tropical moisture to the landfalling ARs, different numerical methods have been applied in the last decades, namely analytical, Lagrangian, and Eulerian models (e.g., Gimeno et al, 2012, for a detailed review). Lagrangian models have been widely used in climatic studies of atmospheric water vapor sources and in the diagnosis of the origin of moisture in extreme precipitation events James, 2004, 2005;Gimeno et al, 2010;Ramos et al, 2016). These models, although widely used, cannot correctly describe evaporation (e) and precipitation (p), in addition to neglecting liquid water and ice, which results in an overestimation of both e and p. All Lagrangian models consider constant parcel volumes.…”
Section: Introductionmentioning
confidence: 99%